DEVELOPMENT AND EVALUATION OF ANTI-ACNE GEL CONTAINING GARLIC (ALLIUM SATIVUM) AGAINST PROPIONIBACTERIUM ACNES - Saptarini, Nyi Mekar; Herawati, Irma Erika (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study is to develop and evaluate the gel of garlic juice as anti-acne to facilitate the topical usage. Methods: The steps of this study consisted of extraction, gel formulations with various concentrations of carboxymethyl cellulose (CMC), and gel evaluation, i.e., organoleptic, viscosity, pH, skin irritation test, hedonic test, and anti-acne activity assay against Propionibacterium acnes. Results: The garlic juice contains alkaloids, saponins, tannins, monoterpenes, and sesquiterpenes. The different concentrations of CMC produce different physicochemistry properties of the gels. These properties were affected the gels stability, anti-acne activity, and the panelis perception on hedonic test. Conclusion: The garlic juice at 7.5% has anti-acne activity to P. acnes, and the gel of 3% CMC is the most stable and preferable.